The Intricate Interplay between Cancer Stem Cells and Oncogenic miRNAs in Breast Cancer Progression and Metastasis - Antonis Tsintarakis; Chara Papalouka; Christina Kontarini; Panagiotis Zoumpourlis; Konstantinos Karakostis; Maria Adamaki; Vassilis Zoumpourlis (Life, 2023)
Complex signaling interactions between cancer cells and their microenvironments drive the clonal selection of cancer cells. Opposing forces of antitumor and tumorigenic potential regulate the survival of the fittest clones, while key genetic and epigenetic alterations in healthy cells force them to transform, overcome cell senescence, and proliferate in an uncontrolled manner. Both clinical samples and cancer cell lines provide researchers with an insight into the complex structure and hierarchy of cancer. Intratumor heterogeneity allows for multiple cancer cell subpopulations to simultaneously coexist within tumors. One category of these cancer cell subpopulations is cancer stem cells (CSCs), which possess stem-like characteristics and are not easily detectable. In the case of breast cancer, which is the most prevalent cancer type among females, such subpopulations of cells have been isolated and characterized via specific stem cell markers. These stem-like cells, known as breast cancer stem cells (BCSCs), have been linked to major events during tumorigenesis including invasion, metastasis and patient relapse following conventional therapies. Complex signaling circuitries seem to regulate the stemness and phenotypic plasticity of BCSCs along with their differentiation, evasion of immunosurveillance, invasiveness and metastatic potential. Within these complex circuitries, new key players begin to arise, with one of them being a category of small non-coding RNAs, known as miRNAs. Here, we review the importance of oncogenic miRNAs in the regulation of CSCs during breast cancer formation, promotion and metastasis, in order to highlight their anticipated usage as diagnostic and prognostic tools in the context of patient stratification and precision medicine.